Physical activity and perceived benefits, but not barriers, to exercise differ by sex and school year among college students. Issue 5 (22nd June 2022) - Frederick, Ginny M.; Williams, Ewan R.; Castillo-Hernández, Isaura M.; Evans, Ellen M.
Abstract: Objective: To assess whether sex or school year influence physical activity and exercise (PA/EX) behaviors and perceived benefits and barriers of PA/EX among college students. Participants: Participants were 862 (78% female; 20.1 ± 1.4 years) college students. Methods: The International Physical Activity Questionnaire, Exercise Benefits and Barriers Scale, and resistance training (RT) questions were completed online. Results: Factorial ANOVA (sex x year) determined no significant interaction effects of sex and school year in behaviors or perceived benefits and barriers (all p  > .05). Males reported higher levels of PA/EX and RT than females ( p  < .05) with no differences by school year ( p  = .34). Benefits Scale scores and some of its subscales were higher for males and first-year students compared to females and third- and fourth-year students (all p  < .05). Conclusion: PA/EX promotion programs may need to be tailored differently based on sex and school year.